Influence of micro-alloying with yttrium and hafnium on the strength characteristics and morphology of the carbide phase of the ZHS3DK-VI alloy during delayed crystalization - Татьяна Владимировна Тихомирова; Елена Ивановна Гордиенко; Руслан Васильевич Бехтер; Александр Витальевич Подобный (Авіаційно-космічна техніка та технологія, 2021)
There are analyzed the melts of the ZhS3DK-VI alloy with different levels of strength characteristics and the factors influencing their reduction, differences in the macro and microstructure of the alloy, the effect of the crystallization rate when pouring the melt into hot and cold ceramic molds are determined. Since when casting parts, the level of properties is determined on separately cast samples, in the technology of manufacturing samples, the casting parameters of the corresponding part must be observed, and when increasing the strength characteristics due to changing technological parameters, it is imperative to consider the possibility of changing the technology of casting parts. However, for parts of complex configuration, cast from heat-resistant nickel alloys, it is often impossible to change the technology, therefore the only way to influence the properties of the material is to use microalloying with rare earth elements, for example, yttrium and hafnium. The introduction of these alloying elements in small amounts has a positive effect on factors that reduce the properties of the ZhS3DK-VI alloy, such as the unfavorable shape and topography of the carbide phase, or even slightly change the chemical composition of carbides. The article analyzes the effect of microalloying with hafnium and yttrium on the morphology and topography of the carbide phase; positive changes in the microstructure and strength characteristics at room temperature of the heat-resistant nickel alloy ZhS3DK-VI are noted. The technology of microalloying the melt has been developed to obtain satisfactory valuesof strength characteristics in tensile tests and impact toughness at room temperature. Microalloying the ZhS3DK-VI alloy with hafnium in a concentration of 0.15...0.25 % made it possible to increase the strength characteristics on samples for mechanical tests by 10…15 %, provided that the melt was drained into hot ceramic molds and slowed down. Higher concentrations of hafnium during slow crystallization lead to the formation of eutectic phases uncharacteristic for the ZhS3DK-VI alloy, requiring a decrease in the heat treatment temperature, which, accordingly, leads to a decrease in the level of long-term strength at 850 °C.